Guidelines for cleaner production implementation and management in the plastic footwear industry - Filho, José Carvalho; Nunhes, Thaís Vieira [UNESP]; Oliveira, Otávio José [UNESP] (Elsevier, 2019)
The environment is the natural source of resources to meet human needs, and processing companies are known to be the main consumers of natural resources. As a result of the productive activities of the companies, the environment has been highly impacted by the loss of non-renewable resources and the emission of polluting waste and gases. The purpose of this article is to characterize and discuss cleaner production (CP) opportunities and challenges for its implementation in a plastic footwear industry. The study was based on a literature review (section 2), which guided the case study analysis in the practical context of six Brazilian footwear plants. The cross analysis of these case studies (section 4), together with the elements identified in the literature, allowed the identification and discussion of CP opportunities and challenges (section 5) particularly suitable for use in the footwear industry. This study contributes with practical suggestions of how footwear plants can mitigate their impacts on the environment by implementing elements of CP. Further, this study opens new avenues of research on CP implementation in this specific sector and present a framework for elaborating guidelines that can be used by other researchers when performing similar case studies.
Keywords: Cleaner production; Environmental efficiency; Footwear industry; Waste management; Water management